Can Meropenem E-test be Used to Estimate the Presence of Carbapenem Resistance Gene cfiA Among Bacteroides fragilis Strains? - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2011)
Bacteroides fragilis, which is found in normal colon flora, is the most commonly encountered pathogen in anaerobic infections and more resistant to antimicrobial agents than the other anaerobes. Limited number of antibiotics; such as carbapenems, beta-lactam/beta-lactamase inhibitors and nitro-imidazoles are the most effective antibiotics against Bacteroides, however resistant isolates to these antimicrobials have been reported recently. Resistance against carbapenems occurs due to a metallo-beta-lactamase enzyme expressed by cfiA gene. While agar dilution method is used to test the antimicrobial susceptibility of anaerobic organisms, E-test is recommended for susceptibility testing of anaerobes associated with life-threatening infections with high mortality and morbidity. In this study, meropenem E-test was used to determine the carbapenem resistance of B.fragilis strains and to estimate the presence of cfiA gene. A total of 63 B.fragilis strains that were previously isolated from clinical samples (of which 16 were from stool samples) in our laboratory, were enrolled in the study. Minimum inhibitory concentration (MIC) values were determined by meropenem E-test (AB Biodisk, Sweden) and presence of cfiA genes were investigated by in-house polymerase chain reaction. The MIC ranges of meropenem were < 0.002 - > 32 mu g/ml and the resistance rate was 9.5% (6/63). Thirty-three percent (21/63) of strains harboured cfiA gene. A statistically significant relation (p< 0.0001) was determined between presence of cfiA gene and high MIC value (MIC >= 0.5 mu g/ml). The proportion of cfiA-positive isolates detected in this study was substantially higher than that reported in other countries. This might be attributed to the frequent use of carbapenems in our hospital. The results of this study indicated that meropenem E-test method could be useful to estimate the presence of cfiA gene in B.fragilis strains and thus to detect the resistant strains.
Keywords: Bacteroides fragilis; metallo-beta-lactamase; cfiA gene; meropenem; E-test; SUSCEPTIBILITY; PREVALENCE; ANAEROBES; SEQUENCE